EVOLUTION OF MOIST POTENTIAL VORTICITY DURING A WARM-ZONE HEAVY RAINFALL EVENT IN THE PEARL RIVER DELTA - 叶爱芬 李江南 徐永辉 伍志方 何如意 蔡榕硕 (Journal of Tropical Meteorology, 2011)
First,based on routine meteorological data,the synoptic characteristics of a heavy warm-sector rainfall that occurred on June 13,2008 in the Pearl River Delta were analyzed.Second,a mesoscale numerical model,Weather Research and Forecasting（WRFV2.2）,was used to simulate the heavy rainfall. Diagnostic analyses were done of moist potential vorticity（MPV）for its horizontal components（MPV2） and vertical components（MPV1）based on the simulation results of WRFV2.2 to identify the mechanism of the rainfall development.The results showed that the heavy rainfall occurred when there were high MPV1 in the upper levels and low MPV1 and high MPV2 in the lower levels.Disturbances of high MPV1 in the upper levels came from the southwest or northwest,those of low MPV1 in the lower levels came from the southwest,and those of high MPV2 came from the south.Disturbances of low MPV1 at low levels were the direct cause of convective instability.Enhanced vertical shear of meridional wind led to increased MPV2 at lower levels,strengthened baroclinicity,and active warm and wet flows.These distributions of MPV helped to trigger the release of unstable energy and produce warm-sector heavy rainfall.As it integrates the evolution of dynamic and thermal fields,MPV is able to reveal the development of this heavy rainfall effectively.